A Peningkatan Hasil Belajar SKI Melalui Metode Bernyanyi pada Siswa Kelas III di MIM Delegtukang Wiradesa - Rif'iyati, Dian (STIT Pemalang, 2024)
The study is set in the background by the observations that the writer made at mim's most salesman. Based on the results of a pre-islamic cultural history course (SKI) study past events, the majority of the materials listed in the book are more memorizing points. Hence there are several results of low student study. And so, teachers come up with the creative idea of singing in future learning. The purpose of the study is to explain the method of singing at the class III MIM Delegtukang Wiradesa, and also to describe the increased results of ski study by using the singing method on class III MIM Delegtukang Wiradesa. The method of study used was class action (PTK) research. Based on the results of the study shown the following results: this was proven by a significant increase in the beginning of the study of precycle-cycle, which still used the talk method, was only 12.5% students, and then after using the method of singing in student studies, the I 70% increased, and the cycle II increased to 87.5%. The occurrence is a 75% increase from pre-cycle to cycle ii. After reaching the target success indicator is 85% and in this study results in 87.50%. Then it is no longer necessary for the III cycle or the continued cycle. From these results it may be concluded that the application of singing methods can improve students' learning on ski subjects in class III MIM Delegtukang Wiradesa.